Associations of daily sleep duration and dietary macronutrient consumption with obesity and dyslipidemia in Koreans: A cross-sectional study. Issue 45 (November 2016) - Doo, Hyungie; Chun, Hyejin; Doo, Miae
Abstract : Abstract: Daily sleep duration is known to be associated with obesity and dyslipidemia. This study was performed to examine the interactions between daily sleep duration and the risks of obesity and dyslipidemia according to dietary macronutrient consumption in 14, 680 Korean adults using the 5th Korean National Health and Nutrition Examination Survey. Sleep duration was inversely associated with body mass index ( P  < 0.001), waist circumference ( P  < 0.001), total cholesterol ( P  < 0.001), and low-density lipoprotein -cholesterol ( P  = 0.001). Participants with short sleep durations consumed less dietary protein ( P  < 0.001) and fat ( P  < 0.001), and consumed more dietary carbohydrates ( P  < 0.001). Among participants with the shortest sleep duration (⩽5 hours a day), the odds ratio of obesity was found to increase in the high fat consumption group (1.393, 95% confidence interval 1.083–1.790) and decrease in the high carbohydrate consumption group (0.770, 95% confidence interval 0.604–0.983). High fat and low carbohydrate consumption were confirmed to be associated with the risk of obesity in the shortest sleep duration group (⩽5 hours a day). These findings indicate that sleep duration was negatively associated with obesity and dyslipidemia-related indices in Korean adults. Additionally, the association of short sleep duration with the risk of obesity was potentially changed by dietary fat and carbohydrate consumption.